2004
DOI: 10.1002/em.20010
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity modulation by cadmium treatment: Studies in the Drosophila wing spot test

Abstract: The genotoxic activity of cadmium chloride (CC) has been evaluated in the somatic mutation and recombination test (SMART) in Drosophila melanogaster. In addition, its possible modulating effect on the genotoxicity of two known mutagenic agents, potassium dichromate (PDC) and ethyl methanesulfonate (EMS), was investigated. Three different types of combined treatments of CC with the two genotoxins were performed: pretreatment, cotreatment, and posttreatment. The SMART assay is based on the principle that loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The average spontaneous frequency of total spots (0.40) was consistent with the historical water control frequency observed in our laboratory, and was in good agreement with the normal range of background frequencies previously reported by different authors [Frei and Würgler, 1995;Torres et al, 1998;Rizki et al, 2004]. EMS (1 mM), the positive control, significantly increased the frequency of all categories of spots.…”
Section: Genotoxicity Of Dma In the Smart Assaysupporting
confidence: 92%
See 1 more Smart Citation
“…The average spontaneous frequency of total spots (0.40) was consistent with the historical water control frequency observed in our laboratory, and was in good agreement with the normal range of background frequencies previously reported by different authors [Frei and Würgler, 1995;Torres et al, 1998;Rizki et al, 2004]. EMS (1 mM), the positive control, significantly increased the frequency of all categories of spots.…”
Section: Genotoxicity Of Dma In the Smart Assaysupporting
confidence: 92%
“…This organism is widely used in genotoxicity studies and, in particular, for the somatic mutation and recombination test (SMART; also known as the Drosophila wing spot test) [Graf et al, 1984]. The SMART is a powerful system for detecting mutation and recombination in somatic cells, as well as for discovering possible interactions between chemicals [e.g., Rizki et al, 2001Rizki et al, , 2002Rizki et al, , 2004. Previous studies indicate that inorganic sodium arsenite is inactive in the Drosophila SMART assay [Ramos-Morales and Rodriguez-Arnaiz, 1995;Rizki et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit fly Drosophila melanogaster with its well development array of genotoxicity test systems has been used in a number of studies on the modulatory effects of various compounds, along with somatic mutation and recombination tests (SMART) have been employed (Graf et al, 1998;Kaya et al, 2002;Rizki et al, 2004;Sinigaglia et al, 2004;Romero-Jiménez et al, 2005;Costa and Nepomuceno, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…This would confirm that the comet assay is more sensitive than the wing-spot assay (Alaraby et al, 2014). In fact, non-genotoxic effects of CdCl 2 in Drosophila using the wing-spot test were observed early by our group (Rizki et al, 2004). Indirect genotoxicity of QDs in Drosophila has already been determined by means of the tunnel assay (Galeone et al, 2012) and positive effects of CdCl 2 have been reported in midgut cells (Shukla et al, 2011) and in hemocytes of spiders fed with Drosophila treated with CdCl 2 (Stalmach et al, 2014).…”
Section: Hsp70mentioning
confidence: 56%